Rekonsiliasi Kosmis melalui Tradisi “Nahe Biti”: Tinjauan Etika Diskursus Penyelesaian Konflik Komunal - Fivo Freitas; Hamka Naping; Yahya Yahya; muhammad Basir; Jayana Suryana Kembara (Universitas Cenderawasih, 2026)
The resolution of communal conflicts at the grassroots level often reaches an impasse when relying solely on the state's positive-retributive legal approach, which tends to overlook the psychological and cultural restoration of the community. In Timor-Leste and its border regions, the traditional practice of Nahe Biti (